Prognostic value of left ventricular hemodynamic forces in patients with left ventricular noncompaction. (3rd October 2022) - Gonzalez Del Hoyo, M; Casas Masnou, G; Romero, A; Azpiroz-Franch, M J; Larranaga Moreira, J M; Escalona Silvina, R A; Guala, A; Limeres Freire, J; Bayes De Luna, A; Zorio Grima, E; Villacorta Arguelles, E; Garcia Pavia, P; et al.
Abstract: Introduction: Left ventricular noncompaction (LVNC) is a poorly defined entity with LV ejection fraction (LVEF) being the main predictor of major adverse cardiovascular events (MACE). Left ventricular hemodynamic forces (LVHDF) have been recently demonstrated to be promising markers of sub-clinical dysfunction and potential predictors of disease outcome. Purpose: To determine in a large cohort of LNVC the LVHDF parameters and its long-term prognostic value. Methods: Retrospective, longitudinal, multicentre cohort study including consecutive patients with LVNC from 2000 to 2018. CMR was performed at 1.5T and LVHDF were analyzed with a prototype software (Medis Suite Qstrain). Systolic LVHDF were decomposed into "apex-base" (long-LVHDF) and "lateral-septal" (radial-LVHDF). MACE was defined as a composite of heart failure (HF), ventricular arrhythmias (VA), systemic embolisms (SE) and/or all-cause mortality. Results: A total of 158 patients were included, age was 53±4.3y and 85 (53.8%) were men. Median LVEF was 44 (IQR 34–55)%, with 61.4% having a LVEF <50%. During a median follow-up of 3.7 (IQR 1.4–5.9) years, MACE occurred in 49 (31%) patients with an unadjusted incidence rate of 8.05 (95% CI 6.0–10.6) events per 100 person-years: 36 HF, 15 VA, 5 SE and 2 deaths. Patients with MACE had significantly worse LVHDF parameters (Table 1). LV-HDF parameters showed no significant variation with age or gender. Spearman coefficient confirmed an inverse correlation between LVEF and long-LVHDF (r=0.478, p<0.0001) and radial-LVHDF (r=0.414, p<0.001). Patients with LVEF <50% (53% vs 78%, p logrank = 0.028) and long-LVHDF <11% (38% vs 84%, p logrank <0.001) had an increased risk of MACE. LVEF (HR 0.97, 95% CI 0.95–0.99, p=0.016), long-LVHDF<11% (HR 5.18, 95% CI 1.1–13.1, p=0.001) and age (HR 1.16, 95% CI 1.06–1.26, p=0.002) were the only variables independently associated with MACE on multivariate analysis. Among patients with LVEF >50%, on univariate regression long-LVHDF <11% (HR 3.32, 95% CI 1.00–11.01, p=0.050) was independently associated with MACE, while LVEF was not (HR 1.04, 95% CI 0.97–1.10, p=0.200). In patients with LVEF <50%, long-LVHDF <11% (HR 7.70, 95% CI 2.40 25.21, p=0.001), and LVEF (HR 0.93, 95% CI 0.90–0.95, p<0.001) were independent predictors of outcome on univariate analysis. Conclusions: LVHDF in patients LVNC were quantified for the first time, with an adequate correlation with LVEF. Both radial and longitudinal LVHDF were significantly reduced in patients with MACE, however, only misalignment of systolic longitudinal-LVHDF predicted outcomes. In patients with LVEF >50%, reduced longitudinal-LVHDF was associated with prognosis, while LVEF was not, and may serve as an additional tool for risk stratification. Funding Acknowledgement: Type of funding sources: None.